Dampak Social Media Marketing, Influencer Marketing, dan Live Streaming Shopping Terhadap Keputusan Pembelian Cetaphil pada Tiktok Shop - Nazwa Ayu Khairani; Amron Amron; Artha Febriana; Hertiana Ikasari (El-Mal: Jurnal Kajian Ekonomi & Bisnis Islam, 2026)
The research aims to examine how Social Media Marketing, Influencer Marketing, and Live Streaming Shoppings on consumers’ purchasings decision regarding Cetaphil product on TikTok Shop platform. The sampling technique employed was purposive sampling, targeting respondents who actively use TikTok, have been exposed to promotional content for Cetaphil products, and have prior experience purchasing through TikTok Shop. This data collected using questionnaires, also the analysis is conducted with SmartPLS 4.0 utilizing Partials Least Squares Structural Equations Modeling (PLS-SEM) method. The result indicate the Social Media Marketing, Influencer Marketing, and Live Streaming Shopping exert a positive and significant effect on purchasing decisions. These finding suggest thats marketing efforts delivered through creative social media content, the involvement of highly credible influencers, and real-time interaction facilitated by live streaming effectively encourage consumers to purchase Cetaphil products on TikTok Shop. Consequently, the integration of social media marketing, influencer marketing, and live streaming strategies is considered increasingly effective in enhancing consumer purchasing decision for Cetaphil products onTikTok Shop platform.